Studi Korelasional Antara Kepemimpinan Kepala Sekolah Dan Budaya Organisasi Dengan Kepuasan Guru - Isman Kadar (MAGMA : JURNAL MAGISTER MANAJEMEN, 2013)
This research can be classified in a correlational study that consists of two independent variables, namely the Principal Leadership and Organizational Culture and one dependent variable, namely Teacher Job Satisfaction. This study was conducted at five state Senior High Schools at South Tangerang City in 2012 with total sample of 129 people taken with proportional random sampling technique. The method used is survey and data analysis techniques using correlation and regression statistical. The hypothesis testing performed on the significant level of 0.05 and 0,01. The results of the study showed that: First, there is positive and highly significant correlation between principals leadership with teachers job satisfaction with correlation coefficient, ry12 = 0,3329 and regression equation ?= 42,392+0,681X1. Second, there is positive and highly significant correlation between organizational culture with teacher job satisfaction, with correlation coefficient ry22=0,34,5, and regression equation ?=45,739+0,655X2. Third, there is positive and highly significant correlation between principal leadership and organizational culture all together with teacher job satisfaction with correlation coeficient ry.122 = 0,475, and regression equation, ?=24,757+0,468X1+0,305X2. Based on the result above it can be concluded that teachers job satisfaction can be improved through principal's leadership and organizational culture.Keywords : teachers job satisfaction, principal's leadership and organizational culture .